2017
DOI: 10.3389/fmicb.2017.02138
|View full text |Cite
|
Sign up to set email alerts
|

The Bacillus subtilis Conjugative Plasmid pLS20 Encodes Two Ribbon-Helix-Helix Type Auxiliary Relaxosome Proteins That Are Essential for Conjugation

Abstract: Bacterial conjugation is the process by which a conjugative element (CE) is transferred horizontally from a donor to a recipient cell via a connecting pore. One of the first steps in the conjugation process is the formation of a nucleoprotein complex at the origin of transfer (oriT), where one of the components of the nucleoprotein complex, the relaxase, introduces a site- and strand specific nick to initiate the transfer of a single DNA strand into the recipient cell. In most cases, the nucleoprotein complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 53 publications
4
16
0
Order By: Relevance
“…Members of the superfamily of RHH transcription factors are involved in the regulation of diverse bacterial processes such as amino-acid biosynthesis, cell division, control of plasmid copy number and lytic cycle of bacteriophages (for review see, 46). Recently, we have shown that many auxiliary relaxosome proteins encoded by conjugative plasmids of G+ bacteria are also RHH type proteins (22). Here we show that Reg 576 too is a RHH type protein, thereby expanding even further the range of processes in which this family of proteins is involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of the superfamily of RHH transcription factors are involved in the regulation of diverse bacterial processes such as amino-acid biosynthesis, cell division, control of plasmid copy number and lytic cycle of bacteriophages (for review see, 46). Recently, we have shown that many auxiliary relaxosome proteins encoded by conjugative plasmids of G+ bacteria are also RHH type proteins (22). Here we show that Reg 576 too is a RHH type protein, thereby expanding even further the range of processes in which this family of proteins is involved.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophoretic mobility shift assay (EMSA) assays were essentially performed as described before (22). In short, 120 ng of the polymerase chain reaction fragment was incubated for 20 min at RT in Binding Buffer (20 mM Tris HCl [pH 8.0], 1 mM EDTA, 5 mM MgCl 2 , 100 mM KCl, 10% (v/v) glycerol) without and with increasing amounts of purified His (6) Reg 576 in a total volume of 20 μl.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the common helix-turn-helix motif for DNA binding, RHH domains bind DNA via a small N-proximal β-sheet composed of one β-strand from each monomer (Schreiter and Drennan, 2007). So far, no accessory factors of G + origin have been structurally characterized, albeit one in silico analysis has indicated that many of them also contain RHH-binding domains (Miguel-Arribas et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…pLS20, a conjugative plasmid isolated from B. subtilis natto [ 19 ], can transfer itself to various B. subtilis -related Gram-positive bacteria, including Bacillus anthracis , Bacillus cereus , Bacillus licheniformis , Bacillus megaterium , Bacillus pumilus , and Bacillus thuringiensis [ 20 ]. pLS20cat, a derivative of pLS20 carrying a chloramphenicol resistance gene possesses the outstanding ability of rapid transfer: after simply mixing liquid cultures of donor and recipient cells the plasmid is efficiently transferred within 15 min [ 21 26 ]. In addition, pLS20cat can mobilize a co-resident plasmid if it contains a functional copy of the oriT of pLS20cat ( oriT LS20 ) [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…pLS20cat, a derivative of pLS20 carrying a chloramphenicol resistance gene possesses the outstanding ability of rapid transfer: after simply mixing liquid cultures of donor and recipient cells the plasmid is efficiently transferred within 15 min [ 21 26 ]. In addition, pLS20cat can mobilize a co-resident plasmid if it contains a functional copy of the oriT of pLS20cat ( oriT LS20 ) [ 26 , 27 ]. Plasmid pLS20 or a derivative has been used to mobilize plasmids in various studies [ 20 , 28 30 ].…”
Section: Introductionmentioning
confidence: 99%